2002
DOI: 10.1152/japplphysiol.00077.2001
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypoxia upregulates connexin43 expression in rat carotid body and petrosal ganglion

Abstract: Recent studies have demonstrated that oxygen-sensitive type I cells in the carotid body express the gap junction-forming protein connexin43 (Cx43). In the present study, we examined the hypothesis that chronic exposure to hypoxia increases Cx43 expression in type I cells as well as in chemoafferent neurons in the petrosal ganglion. Immunocytochemical studies in tissues from normal rats revealed diffuse and granular Cx43-like immunoreactivity in the cytoplasm of type I cells and dense punctate spots of immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Other investigators have shown Cx43 expression can increase (ie, in the carotid body and petrosal ganglion) 20 or decrease (ie, in cultured astrocytes) 21 in response to hypoxia; however, the underlying mechanism of this regulation remains unknown. Remarkably, by suppressing the hypoxia-induced elevation in ROS formation in smooth muscle cells by either a mitochondrial complex I inhibitor (rotenone) or a glutathione peroxidase mimic (ebselen), the ensuing rise in Cx43 protein levels and gap junction channel permeability could be largely prevented.…”
Section: Discussionmentioning
confidence: 98%
“…Other investigators have shown Cx43 expression can increase (ie, in the carotid body and petrosal ganglion) 20 or decrease (ie, in cultured astrocytes) 21 in response to hypoxia; however, the underlying mechanism of this regulation remains unknown. Remarkably, by suppressing the hypoxia-induced elevation in ROS formation in smooth muscle cells by either a mitochondrial complex I inhibitor (rotenone) or a glutathione peroxidase mimic (ebselen), the ensuing rise in Cx43 protein levels and gap junction channel permeability could be largely prevented.…”
Section: Discussionmentioning
confidence: 98%
“…However, P2X 2 blockaded did not completely eliminate the response to hypoxia in either condition indicating that ATP acts in concert with other excitatory mechanisms in the carotid body. This could be an excitatory neurotransmitter, such as ACh discussed above, or perhaps enhanced electrical coupling between glomus cells and afferent nerve terminals considering that chronic hypoxia up-regulated gap junction proteins (connexin-43) in carotid bodies (Chen et al, 2002a).…”
Section: Neurochemicalsmentioning
confidence: 99%
“…It has been reported that hypoxia regulates Cx43 expression and channel activity in different cell models (20,21). However, no data are currently available addressing the role of Cx43 channels in melanoma cells in the context of the hypoxic microenvironment and their putative involvement in tumor cell susceptibility to NK cell-mediated lysis.…”
mentioning
confidence: 99%